SIMLABS TECHNOLOGY 2.0 IN IMPROVING VOCABULARIES FOR ELEMENTARY SCHOOL TEACHER BILINGUAL CLASS - Ulhaq Zuhdi; Neni Mariana; Mintohari Mintohari; Susan Ledger; John Fiscetti; Natasha Rappa (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2022)
In Microteaching 2.0, virtual students are provided using interactor by SimLab Murdoch University staff. These virtual students can immediately respond to students who practice teaching in front of them. The collaboration between Murdoch University and Unesa brings Simlab technology to be tested on bilingual class students of PGSD Unesa. This Microteaching 2.0 technology has also collaborated at the University of Newcastle, Australia. this collaborative research collaboration was carried out with two universities, Murdoch University and Universitas Negeri Surabaya. The purpose of this study is to describe the new vocabularies that can be improved by bilingual class PGSD students through SimLab.